Abilities, Skills, and Attitudes toward Educational Research of Social Studies Students at the Faculty of Education, Phuket Rajabhat University - Rujikittioangsuthon, Somporn (ASEAN Journal of Education, 2023)
The purposes of this study were to explore the skills and attitudes of research for students majoring in social studies at Faculty of Education and to propose a method for improving research abilities. The study revealed that students’ research abilities could be enhanced by organizing a training workshop in addition to classroom pedagogy and hands-on research. Courses in social studies should include suitable and regular instruction or training plans to boost students’ research skills. This research also offered suggestions for improving educational research abilities, such as research knowledge, skills, and a positive attitude toward research. More specificall , students should be encouraged to conduct research of their interest, and should have the opportunity to conduct research within the appropriate time frame to maximize their research skills.